Effects of interorganisational information technology networks on patient safety: a realist synthesis. Issue 10 (10th October 2020) - Keen, Justin; Abdulwahid, Maysam Ali; King, Natalie; Wright, Judy M; Randell, Rebecca; Gardner, Peter; Waring, Justin; Longo, Roberta; Nikolova, Silviya; Sloan, Claire; Greenhalgh, Joanne
Abstract : Objective: Health services in many countries are investing in interorganisational networks, linking patients' records held in different organisations across a city or region. The aim of the systematic review was to establish how, why and in what circumstances these networks improve patient safety, fail to do so, or increase safety risks, for people living at home. Design: Realist synthesis, drawing on both quantitative and qualitative evidence, and including consultation with stakeholders in nominal groups and semistructured interviews. Eligibility criteria: The coordination of services for older people living at home, and medicine reconciliation for older patients returning home from hospital. Information sources: 17 sources including Medline, Embase, CINAHL, Cochrane Library, Web of Science, ACM Digital Library, and Applied Social Sciences Index and Abstracts. Outcomes: Changes in patients' clinical risks. Results: We did not find any detailed accounts of the sequences of events that policymakers and others believe will lead from the deployment of interoperable networks to improved patient safety. We were, though, able to identify a substantial number of theory fragments, and these were used to develop programme theories. There is good evidence that there are problems with the coordination of services in general, and the reconciliation of medication lists in particular, and it indicates that most problems are social and organisational in nature. There is also good evidence that doctors and other professionals find interoperable networks difficult to use. There was limited high-quality evidence about safety-related outcomes associated with the deployment of interoperable networks. Conclusions: Empirical evidence does not currently justify claims about the beneficial effects of interoperable networks on patient safety. There appears to be a mismatch between technology-driven assumptions about the effects of networks and the sociotechnical nature of coordination problems. PROSPERO registration number: CRD42017073004.